PERLINDUNGAN HUKUM TERHADAP KONSUMEN YANG TIDAK MENERIMA PEMBELIAN PRODUK JASA BERUPA TIKET KONSER DARI PELAKU USAHA MELALUI MEDIA SOSIAL DITINJAU DARI UNDANG-UNDANG NOMOR 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN - Elisabeth Haryani; Jeane Neltje (Jurnal Hukum Adigama, 2021)
Over time, the purchase of goods/services can now be made online. One of them is the various type of services offered by business entities to the consumers. Proxy purchase/parallel trade/on-selling is one of the services sought by customers to fulfill their needs and wants. In this case, consumers use ticket on-seller service to obtain a concert ticket. Ticket on-selling offered through social networking sites often does not go smoothly and caused losses to the consumer. Therefore, consumers need legal protection to protect their rights and signify what kind of responsibility should be borne to the business entity that does not fulfill its promise. Referring to the case, the author conducted a study using the normative method. The result of the study suggested that the consumer can file lawsuits in court or resolve disputes outside the courts through authorized institutions. Considering that there are currently no regulations regarding electronic commerce and transaction over social networking sites, the author also suggests that the government make special regulations regarding electronic commerce to avoid similar transactions involving electronic system transactions.